(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:The study focused on acute stage of stroke patients and investigated which parameters of glucose in acute phase of stroke are significant in nondiabetic stroke patients. Objective:To evaluate hyperglycaemia in acute phase of stroke. Methods:Cross sectional study was conducted in Al-Imamain Al-Kadhimiyan Medical City in Baghdad city from October 2013 to September 2014. We studied glucose levels and glycosylated haemoglobin in 100 consecutive patients with acute stroke admitted within 24 hours after onset of symptoms. Results:One hundred consecutive patients (65 men and 35 women ) were included in this study, 76 patients with diagnosis of ischemic stroke and 18 of them with diagnosis of intracerebral haemorrhage and 6 patients with transient ischemic attack Hyperglycemia was found in 44 patient. High glycosylated haemoglobin levels were found in 29 patients, 16 patients of them have history of diabetes. The other 13 with elevated glycosylated haemoglobin levels were considered as prediabetes. The remaining 15 patients had normal glycosylated haemoglobin. Conclusion:There is significant relationship between idiopathic hyperglycemia and prediabetes with acute stroke. Keywords:Stroke, diabetes mellitus, hyperglycaemia